A CONTROL OF OXYGEN SUPPLY IN BIOCONVERSION OF SUGARCANE TRASH INTO XYLITOL BY Meyerozyma guilliermondii InaCCY65 - Thontowi, Ahmad; Kanti, Atit; Listiyowati, Sri; Meryandini, Anja (Berita Biologi, 2024)
Xylitol is a sugar alcohol used as a sugar substitute for several prevention of health cases such as dental diseases, diabetes, and other health problems. Bioconversion of xylose into xylitol needs an optimum oxygen supply for xylitol synthesis. This research aims to determine the effect of dissolved oxygen on hydrolysate fermentation from sugar cane leaf as a source of xylose to xylitol by Meyerozyma guilliermondii InaCCY65. Dissolved oxygen was varied in aeration and fermentation agitation using a 3L scale bioreactor. Analysis of cell growth for several kinetic parameters during fermentation, xylose reductase, and xylitol dehydrogenase activity. Bioconversion of sugarcane trash hydrolysate into xylitol by M. guilliermondii InaCCY65 is influenced by the oxygen transfer coefficient (kLa) and aeration conditions. The increase in kLa number showed increased cell growth, xylose consumption, xylitol production, and decreased InaCCY65 cells. The optimum conditions of kLa were obtained at 45/h with 39 g/L xylitol production under the aeration effect. Optimum aeration in the bioconversion of sugarcane trash (SCT) hydrolysate become xylitol by M. guilliermondii InaCCY65 is 1.0%; under these conditions, xylitol yield and xylitol productivity are 0.78 g/g and 1.20 g/Lh. The effect of oxygen in the bioconversion of xylose to xylitol also has an impact on xylose reductase (XR) and xylose dehydrogenase (XDH) activities of M. guiellermondii InaCCY65. The results showed that the dissolved oxygen concentration must be carefully controlled during xylitol bioconversion to obtain efficient xylitol.